Calcium Concentration in Culture Medium as a Nondestructive and Rapid Marker of Osteogenesis. Issue 6 (June 2017) - Tanikake, Yohei; Akahane, Manabu; Furukawa, Akira; Tohma, Yasuaki; Inagaki, Yusuke; Kira, Tsutomu; Tanaka, Yasuhito
Artificial bones made of β-tricalcium phosphate (β-TCP) combined with bone marrow-derived mesenchymal stromal cells (BM-MSCs) are used for effective reconstruction of bone defects caused by genetic defects, traumatic injury, or surgical resection of bone tumors. However, the selection of constructs with high osteogenic potential before implantation is challenging. The purpose of this study was to determine whether the calcium concentration in BM-MSC culture medium can be used as a nondestructive and simple osteogenic marker for selecting tissue-engineered grafts constructed using β-TCP and BM-MSCs. We prepared three cell passages of BM-MSCs derived from three 7-week-old, male Fischer 344 rats; the cells were cultured in osteoinductive medium in the presence of β-TCP for 15 days. The medium was replaced with fresh medium on day 1 in culture and subsequently changed every 48 h; it was collected for measurement of osteocalcin secretion and calcium concentration by enzyme-linked immunosorbent assay and X-ray fluorescence spectrometry, respectively. After cultivation, the constructs were implanted subcutaneously into the backs of recipient rats. Four weeks after implantation, the alkaline phosphatase (ALP) activity and osteocalcin content of the constructs were measured. A strong inverse correlation was observed between the calcium concentration in the medium and the ALP activity and osteocalcin content of the constructs, with Pearson's correlation coefficients of 0.92 and 0.90, respectively. These results indicate that tissue-engineered bone with high osteogenic ability can be selected before implantation based on low calcium content of the culture medium, resulting in successful bone formation after implantation. This nondestructive, simple method shows great promise for assessing the osteogenic ability of tissue-engineered bone.